2018
DOI: 10.1002/evl3.39
|View full text |Cite
|
Sign up to set email alerts
|

Male-biased gene expression resolves sexual conflict through the evolution of sex-specific genetic architecture

Abstract: Many genes are subject to contradictory selection pressures in males and females, and balancing selection resulting from sexual conflict has the potential to substantially increase standing genetic diversity in populations and thereby act as an important force in adaptation. However, the underlying causes of sexual conflict, and the potential for resolution, remains hotly debated. Using transcriptome‐resequencing data from male and female guppies, we use a novel approach, combining patterns of genetic diversit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
112
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(128 citation statements)
references
References 65 publications
(167 reference statements)
15
112
1
Order By: Relevance
“…; Wright et al. ). An alternative hypothesis is that the evolution of dimorphism has proceeded in the observed direction because it is the direction least constrained by B .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…; Wright et al. ). An alternative hypothesis is that the evolution of dimorphism has proceeded in the observed direction because it is the direction least constrained by B .…”
Section: Discussionmentioning
confidence: 98%
“…For the most dimorphic traits, because all correlational constraints have been resolved, the evolution of further dimorphism would then require a reduction in the diagonal of B. This could be achieved through mechanisms such as sex-biased mutational variation (Sharp and Agrawal 2012), sex-specific dominance effects (Fry 2009), genomic imprinting (Day 2004), or sex specific gene expression (Ingleby et al 2015;Wright et al 2018). An alternative hypothesis is that the evolution of dimorphism has proceeded in the observed direction because it is the direction least constrained by B.…”
Section: Discussionmentioning
confidence: 99%
“…the genes are differentially expressed in the sexes (Charlesworth, 2018;Ellegren & Parsch, 2007;Papa et al, 2017;Wright et al, 2018), and various epigenetic mechanisms have been suggested that could facilitate such expression variation (Allis & Jenuwein, 2016;Grath & Parsch, 2016;Holoch & Moazed, 2015).…”
mentioning
confidence: 99%
“…Initial studies calculated differentiation between females and males using Wright's fixation index (F ST ), and interpreted high values as evidence of sexually antagonistic selection. Empirical data from multiple taxonomic groups (Lucotte et al 2016;Flanagan and Jones 2017;Wright et al 2018;Dutoit et al 2018) suggest that hundreds to thousands of SNPs have elevated male-female autosomal differentiation with outliers exceeding F ST = 0.01 (Lucotte et al 2016;Wright et al 2018) and even approaching F ST = 0.2 (Flanagan and Jones 2017). (Cheng and Kirkpatrick 2016) interpreted correlations of male-female F ST with bias in gene expression to mean that many genes actively affect sex-specific viability in both humans and Drosophila melanogaster.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have observed high mean male-female divergences (measured by F ST ). For instance,Dutoit et al (2018) found a mean male-female F ST = 0.0016 across genes with male-biased expression in a sample of 43 flycatchers of each sex Wright et al (2018). found a larger average male-female F ST value of 0.03 across sex-biased genes in transcriptomes of 11 male and four female Trinidadian guppies.Similarly,Flanagan and Jones (2017) identified 473 genome-wide outliers having male-female F ST values above roughly 0.05 in a RADseq study of 171 male and 57 female gulf pipefish.…”
mentioning
confidence: 99%